Ciprofloxacin or Imipenem Use Correlates with Resistance in Pseudomonas aeruginosa - George G Zhanel; Lindsay E Nicolle; Alfred S Gin; James Karlowsky; Amin Kabani; Daryl J Hoban (Canadian Journal of Infectious Diseases)
OBJECTIVE: To investigate the relationship between ciprofloxacin or imipenem use and antimicrobial resistance in Pseudomonas aeruginosa.